Cost-effectiveness analysis of toripalimab combined with nab-paclitaxel as a first-line treatment for advanced TNBC in the US - Ping Chen; Dan Qiao; Liping Xiao; Guiya Deng; Qing Yang; Rendi Tian (PLoS ONE, 2025)
Introduction Initial immunotherapy outcomes with toripalimab suggest a potential paradigm shift in the treatment of advanced triple-negative breast cancer (TNBC), promising extended survival for patients. However, its cost-effectiveness in the treatment of TNBC within the US health care context remains to be determined. Methods A 5-year Markov model was developed using data from the TORCHLIGHT study to evaluate the cost-effectiveness of toripalimab plus nab-paclitaxel as a first-line therapy for metastatic or recurrent TNBC in the US. The model incorporated efficacy and safety data, literature-derived costs and utilities, and calculated ICERs. Sensitivity analyses were conducted to assess the impact of variable uncertainties on the outcomes. Results Toripalimab combined with nab-P chemotherapy for TNBC patients resulted in an additional 2.68 life years (LYs) and 1.72 quality-adjusted life years (QALYs), with an ICER of $593,750 per QALY. Sensitivity analyses indicated that the cost and survival utility of toripalimab significantly influence patient outcomes. At a $100,000/QALY WTP threshold, combination therapy was not cost-effective compared with nab-P alone. Conclusions Our analysis suggests that, from a US health care system perspective, toripalimab in combination with chemotherapy does not demonstrate a significant cost-effective advantage over nab-P chemotherapy as a first-line treatment for patients with TNBC at a WTP threshold of $100,000/QALY and has a limited impact on US health care policy and clinical practice.